Analisis Spasial Jalur Pendakian Gunung Lawu via Cemoro Sewu Berbasis SIG - Andin Ayu Oksilia Ramadhani; Nur Ariesanto Ramdhan; Bambang Irawan (STMIK Banjarbaru, 2026)
This study analyzes the spatial characteristics of the Mount Lawu hiking trail via Cemoro Sewu based on Geographic Information Systems (GIS) by utilizing National Digital Elevation Model (DEMNAS) data. The methods used include the collection of trail and hiking post point data, spatial processing using QGIS, overlay with DEMNAS, as well as elevation profile extraction and slope analysis. The results of the study show that the hiking trail has an elevation range from approximately 1,913 meters to approximately 3,229 meters above sea level with a total elevation gain of around 1,316 meters. Elevation profile analysis shows a gradual increase pattern, with the most significant segment being from Post 1 to Post 2, which has the highest elevation gain. In addition, slope analysis results show that the trail is dominated by moderate to steep slope classes (approximately 23°–30°), especially in the middle sections up to near the summit. The spatial information produced in the form of route maps, elevation profiles, and slope distribution is able to provide a quantitative picture of the difficulty level of the route.Keywords: Geographic information system; Demnas; Hiking trails; Elevation profile; Mount Lawu AbstrakPenelitian ini menganalisis karakteristik spasial jalur pendakian Gunung Lawu via Cemoro Sewu berbasis Sistem Informasi Geografis (SIG) dengan memanfaatkan data Digital Elevation Model Nasional (DEMNAS). Metode yang digunakan meliputi pengumpulan data jalur dan titik pos pendakian, pengolahan spasial menggunakan QGIS, overlay dengan DEMNAS, serta ekstraksi profil elevasi dan analisis kemiringan lereng. Hasil penelitian menunjukkan bahwa jalur pendakian memiliki rentang elevasi dari ±1.913 mdpl hingga ±3.229 mdpl dengan total kenaikan elevasi sekitar ±1.316 meter. Analisis profil elevasi menunjukkan pola kenaikan bertahap dengan segmen paling signifikan berada pada Pos 1–Pos 2 sebagai bagian dengan kenaikan elevasi tertinggi. Selain itu, hasil analisis kemiringan lereng menunjukkan bahwa jalur didominasi oleh kelas lereng sedang hingga curam (±23°–30°), terutama pada bagian tengah hingga mendekati puncak. Informasi spasial yang dihasilkan berupa peta jalur, profil elevasi, dan distribusi kemiringan lereng mampu memberikan gambaran kuantitatif mengenai tingkat kesulitan jalur.